2021
DOI: 10.2147/rmhp.s280393
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Peer Education on Decision-Making, Smoking-Promoting Factors, Self-Efficacy, Addiction, and Behavior Change in the Process of Quitting Smoking of Young People

Abstract: Purpose The study aims to examine the effect of peer education on the decision to quit smoking, factors that encourage smoking, self-efficacy, addiction, and behavior change in students who apply to the Youth Friendly Center to quit smoking. Participants and Methods This research is a Randomized Controlled Trials study. The experimental group consisted of students who were enrolled in the peer education course (n=759). The control group has consisted of students (n=1095… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
(90 reference statements)
1
14
0
Order By: Relevance
“…Confirming the role of health self-efficacy in achieving health behavior change (Jackson et al. , 2007; Orsal and Ergun, 2021), we find that individuals’ high level of health self-efficacy can effectively prompt them to avoid problematic smartphone use.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Confirming the role of health self-efficacy in achieving health behavior change (Jackson et al. , 2007; Orsal and Ergun, 2021), we find that individuals’ high level of health self-efficacy can effectively prompt them to avoid problematic smartphone use.…”
Section: Discussionsupporting
confidence: 57%
“…Echoing previous findings that perceived benefits and barriers are crucial drivers of performing healthy behaviors (Rosenstock, 1974), our results authenticate the positive relationship between perceived benefits and smartphone avoidance intention as well as the negative relationship between perceived barriers and smartphone avoidance intention. Confirming the role of health selfefficacy in achieving health behavior change (Jackson et al, 2007;Orsal and Ergun, 2021), we find that individuals' high level of health self-efficacy can effectively prompt them to avoid problematic smartphone use.…”
Section: Core Findingsmentioning
confidence: 54%
“…The number of smoking cessation clinics is increasing ever since (14). Yet the tobacco consumption rate is still high especially in the younger population (15). According to the latest report of Turkey Statistics Institute tobacco consumption rate increased in the last decade in every age group.…”
Section: What To Come?mentioning
confidence: 99%
“…Baskerville et al, 2018;Epton et al, 2014) Orsal & Ergun (2021). used RCT study design to implement smoking cessation education but only showed 94.1% self-reported rate in the control group.…”
mentioning
confidence: 99%
“…Harris et al (2010) described a self-reported quit rate of 31.4% at post-intervention and a bio-chemically veri ed 30-day abstinence rate of 20.4% at 6 months, which became slightly lower than the control group at 6 months compared to quit rates of 28.0% and 20.4% in the control arm, respectively(Harris et al, 2010). The study conducted byOrsal & Ergun (2021) examined the effects of peer education on the decision to quit smoking, factors that encourage smoking, self-e cacy, and behavior change among students who apply to the Youth Friendly Center to quit smoking. Results showed that participants in the experimental group had a higher quit rate than the control group (p > 0.01) and that 94% of students in the intervention group were free of nicotine addiction and had successfully quit at the seventh and eighth follow-up (p < 0.001).One study provided a booklet-based intervention with a booster phone call(Travis & Lawrance, 2009) with three arms of the RCT study, and this study reported a 11.4% self-reported 7-day abstinence rate at 3-month follow-up, compared to the usual care group or other booklet-based program, which was statistically signi cant.…”
mentioning
confidence: 99%